2023
DOI: 10.29029/busbed.1205026
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Personeli̇ni̇n Di̇ji̇tal Ortamda Sağlik Bi̇lgi̇si̇ Edi̇nme Ve Teyi̇t Davranişlari İle Sağlik Okuryazarliği Bi̇lgi̇ Düzeyi̇ İli̇şki̇si̇ni̇n Beli̇rlenmesi̇

Abstract: Sağlık okuryazarlık düzeyi ile dijital ortamda sağlık bilgisi edinme ve teyit etme davranışları arasındaki ilişkinin belirlendiği bu araştırma belirli bir zaman diliminde gerçekleştiği için kesitsel türde bir çalışmadır. Araştırmada veri niteliğine göre uygun istatistik yöntemleri tercih edilmiştir. Türkiye’de bir üniversite personeli üzerinde gerçekleştirilen bu araştırmada tabakalı örnekleme yöntemi tercih edilmiştir. Elde edilen veriler, SPSS (Statistical Package Program for Social Science) V24.0 yazılım pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…A research carried out with university students reported a linear relationship between students' digital verification behaviors and their interactive health literacy. 16 Correspondingly, Özen et al 30 also emphasized that the verification process of the information reliability acquired by The current study found that the access to information sub-dimension of the health literacy scale substantially influences all sub-dimensions related to the patient empowerment scale. The term 'access to information' refers to the practices, including information gathering, data scanning, and classification, which individuals follow to access relevant information.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A research carried out with university students reported a linear relationship between students' digital verification behaviors and their interactive health literacy. 16 Correspondingly, Özen et al 30 also emphasized that the verification process of the information reliability acquired by The current study found that the access to information sub-dimension of the health literacy scale substantially influences all sub-dimensions related to the patient empowerment scale. The term 'access to information' refers to the practices, including information gathering, data scanning, and classification, which individuals follow to access relevant information.…”
Section: Discussionsupporting
confidence: 53%
“…14 Several studies reported that information acquisition from digital platforms is necessary and effective for patients to adopt behavioral changes and successfully manage the disease to prevent chronic illnesses. [15][16][17] The literature also revealed that health information acquisition from digital media largely favorably impacted chronic illness management -despite a few contradictory citations. 17,18 Therefore, the absence of any study in the literature assessing the relationship between the variables of acquiring and verifying health information in the digital environment, health literacy, and patient empowerment necessitated carrying out the current research.…”
mentioning
confidence: 99%